Students’ Experience on Thesis Writing - Adhikari, Bala Ram (Bhairahawa Campus Journal, 2023)
This article attempts to explore the Master’s Level students’ experience on thesis writing. Two students who had just completed their thesis writing task had been taken as a sample of the study. In-depth interview was used as a tool for data collection. The interview was taken in two phases. The collected information through the in-depth interviews was transcribed and coded to develop the themes. Three themes were developed through this study; thesis writing is challenging and rigorous task, English language has the supporting role in thesis writing and thesis writing as a platform for learning. Through the findings and results it had been concluded that thesis writing is not only inevitable but also desirable for the students for the higher level.